1996
DOI: 10.1021/ic9610748
|View full text |Cite
|
Sign up to set email alerts
|

Metalloporphyrin Mixed-Valence π-Cation Radicals:  Solid-State Structures

Abstract: The synthesis and structural characterization of three mixed-valence π-cation radical derivatives of (octaethylporphinato)metal(II) species, [M(OEP•/2)]2 +, (M = Ni, Cu, and (Zn,H2)), are reported. The species thus have the same formal ring oxidation level as the photooxidized special pair of photosynthetic reaction centers. The complexes display unique binuclear structures with cofacial porphyrin rings with mean plane separations of 3.20−3.32 Å, ring center to ring center distances of 3.50−3.55 Å, and lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 55 publications
0
44
1
Order By: Relevance
“…The high degree of ring-ring overlap in the p-cation radical derivatives, which is much stronger than that seen in the solid-state structures of neutral species [5], suggested that the degree of ring overlap might be related to the oxidation level of the porphyrin ring. This idea was further supported by the degree of overlap found for the structures of three mixed-valence species [22,23]. In these species, which are called mixedvalence species because the one electron that is removed in the ring oxidation appears to be delocalized over two porphyrin rings.…”
Section: Core Conformation Changes and Ring-ring Interactionsmentioning
confidence: 96%
See 1 more Smart Citation
“…The high degree of ring-ring overlap in the p-cation radical derivatives, which is much stronger than that seen in the solid-state structures of neutral species [5], suggested that the degree of ring overlap might be related to the oxidation level of the porphyrin ring. This idea was further supported by the degree of overlap found for the structures of three mixed-valence species [22,23]. In these species, which are called mixedvalence species because the one electron that is removed in the ring oxidation appears to be delocalized over two porphyrin rings.…”
Section: Core Conformation Changes and Ring-ring Interactionsmentioning
confidence: 96%
“…The value of the lateral shift in these three mixed-valence radical derivatives are intermediate to the tightest values seen in the neutral species and the completely overlapped cores of the fMOEP Á g 2 2 dimers. Scheidt et al [23] thus suggested that the ring-ring p-p interactions are sensitive to the oxidation level of the porphyrin ring. Subsequently, it was shown that one form of fNiOEP Á g 2 2 [24] and fMgOEP Á g 2 2 [20] did not conform to this pattern; each of these derivatives has lateral shifts similar to those displayed by tightly interacting neutral species.…”
Section: Core Conformation Changes and Ring-ring Interactionsmentioning
confidence: 99%
“…Further, I would take notice of two bodies of work that have not been discussed in this paper, work on the other oxynitrogen-ligated porphyrins (the ligands NO 2 − and NO 3 − ) [112][113][114][115][116][117][118][119][120][121][122][123][124] and the work on the characterization of π-cation radical complexes [125][126][127][128][129][130][131][132][133][134][135][136][137][138][139]. Diagram Illustrating the effect of axial ligand orientation on the axial bond distances in iron (III) species.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison the two available structures for metal complexes of mono-tertbutylporphyrin exhibit more typical -stacked aggregates. 21 In the nickel(II) derivative Ni(II)2c, with one crystallographically independent molecule in the asymmetric unit, four 'dimers' fill the unit cell with the meso substituents offset by 90º against each other.…”
Section: Manuscript For Tetrahedronmentioning
confidence: 99%